Structure of Mahmud Zamakhari’s Work “Nukatu-L-I’rab” - Abzalova Farida (Penerbit Jurnal Indonesia, 2024)
This article briefly describes the life and scientific activity of Zamakhshari. It also provides information about the scholar's work